Factors Affecting Credit Card Usage - Syed Ahmad, Syed Sharaff (1998)
Spending via the using of credit cards has reached an alarming level and had prompted Bank Negara Malaysia to take some drastic actions including increasing the minimum monthly payment from 5% to 15% and imposing an annual surcharge of RM50.00 per card, to curb the spending. As at June 1996, There were estimated more than 2 million cards issued in this country with a total transaction of RM4.1 billion. This study will make an attempt to find out why do people use the cards and whether the demographic and psychographic factors of the card users have a bearing on their level of usage.